2020
DOI: 10.5194/hess-24-5027-2020
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic influence on the Rhine water temperatures

Abstract: Abstract. River temperature is an important parameter for water quality and an important variable for physical, chemical and biological processes. River water is also used by production facilities as cooling agent. We introduced a new way of calculating a catchment-wide air temperature using a time-lagged and weighed average. Regressing the new air temperature vs. river water temperature, the meteorological influence and the anthropogenic heat input could be studied separately. The new method was tested at fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Although this study was primarily motivated by the fact that thermal refuges are critical habitats for ichthyofauna, the models developed herein may have other applications. They could include other natural phenomena, such as rivers emptying into lakes (Smith & Simpkins, 2018), tributaries affecting the thermal regimes of lakes (Råman Vinnå et al, 2018), and freshwater plumes in estuaries (Huang et al, 2020), or artificial phenomena as man‐made thermal plumes in rivers and coastal environments, where the most common case is likely the discharge of warm‐water effluent from a power plant (e.g., Penk & Williams, 2019; Zavarsky & Duester, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although this study was primarily motivated by the fact that thermal refuges are critical habitats for ichthyofauna, the models developed herein may have other applications. They could include other natural phenomena, such as rivers emptying into lakes (Smith & Simpkins, 2018), tributaries affecting the thermal regimes of lakes (Råman Vinnå et al, 2018), and freshwater plumes in estuaries (Huang et al, 2020), or artificial phenomena as man‐made thermal plumes in rivers and coastal environments, where the most common case is likely the discharge of warm‐water effluent from a power plant (e.g., Penk & Williams, 2019; Zavarsky & Duester, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The final RAPS must be 0 to verify whether the calculation is provided correctly because the time-series counter completes the summation of the time-series members. The authors of [6] concluded that a change in the slope of the RAPS values only indicates a change in the slope size of the original time series. A negative slope for the RAPS does not imply a negative slope in the original time-series.…”
Section: Application Of Rescaled Adjusted Partial Sums (Raps) Methods...mentioning
confidence: 99%